STRENGTHENING THE DSN-MUI FATWA AS A LEGAL SOURCE IN RESOLVING SHARIA ECONOMIC DISPUTES IN INDONESIA - Ali Ramdlani, Abdul Azis (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
This study, titled "Strengthening the DSN-MUI Fatwa as a Legal Source within the Indonesian Legislative System in Resolving Sharia Economic Disputes", is driven by concerns over the lack of binding legal authority of DSN-MUI (National Sharia Council of the Indonesian Ulema Council) fatwas. Despite their valuable content and relevance to Islamic economic practices, these fatwas are not yet formally recognized as binding legal sources. To address this issue, the research raises two main questions: (1) What is the current legal status of DSN-MUI fatwas within Indonesia's regulatory system in resolving sharia economic disputes? and (2) How can these fatwas be strengthened to gain formal legal recognition?. Using a qualitative-normative method through literature review, the study examines both fatwas that have been adopted into legislation and those that have not. The findings reveal that DSN-MUI fatwas, in practice, lack binding legal force in Sharia economic dispute resolution. The study also explores ways to enhance their legal standing. The analysis concludes that: (1) DSN-MUI fatwas do not yet have binding legal power, and their application still faces challenges in legal practice; and (2) Their legal authority can be strengthened by collaborating with state institutions, such as the Supreme Court, to issue judicial regulations (PERMA) that formally incorporate DSN-MUI fatwas. This approach would provide them with stronger legal legitimacy in Indonesia’s regulatory framework